Analisis Terhadap Tindak Pidana Kesehatan Bagi Masyarakat Yang Menolak Melakukan Vaksinasi Covid 19 Berdasarkan Peraturan Presiden Republik Indonesia Nomor 14 Tahun 2021 Jo Undang-Undang Nomor 4 Tahun 1984 Tentang Wabah Penyakit Menular - Dwi Y, Annisa; B, Erlina (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Vaccines are biological products of attenuated or dead viruses. Vaccines are substances or substances that function to help the body fight certain diseases. As for the problems in this study, (1) the factors that cause people who refuse to vaccinate against COVID-19 and (2) criminal sanctions for people who refuse to vaccinate against COVID-19, the research method used is normative and empirical juridical, the results of research on factors causing society refuse vaccination, namely there are still doubts about the safety of the vaccine, want to wait, worry about costs, religious reasons, and feel confident that there is no need for vaccines plus there are hoaxes and criminal sanctions for the community refusing to be threatened with imprisonment for a maximum of 1 (one) year and/or or a maximum fine of IDR 1,000,000 (one million rupiah).